Massively multiplayer online games in Computer Supported Cooperative Work / Ahmad Nazren Ahmad Shahren - Ahmad Shahren, Ahmad Nazren (2017)
Massive Multiplayer Online Game (MMOG) is an online game which capable of supporting large numbers of players. MMOG enables players to cooperate and compete with each other and interact with people around the world. This game can be found of most networks including personnel computer, video games console or smartphones and other mobile device. Most of the game connects the connection using User Datagram Protocols (UDP). Most of the players having difficult to interact with each other due to data loss when playing the game. The reason is that UDP often lose data when a message is being sent and received by the server. So player having difficult to communicate with each other. This thesis includes communication awareness between players when they interact in the game, with the implementation of Unity 3D plug-in as the engine for connect Transmission Control Protocol (TCP). In this project, Computer Supported Cooperative Work will be use as communication between the players are important to the project. It combines the understanding of the way people work with enabling technologies of computer networking, and associated hardware, software, services and techniques. The result of the project will show the gameplay which is Checkers using Unity 3D and interaction between players through chatting while playing.